2020
DOI: 10.21577/0100-4042.20170668
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Analysis and Chemotaxonomic Considerations of Malvoideae (Malvaceae) Species

Abstract: Previous researches showed that fatty acids analysis might be a useful tool to support the taxonomic investigation. In this approach the fatty acids content of ten Malvoideae species was analyzed and its chemotaxonomic significance has been investigated. The aerial parts of the species were collected in the Northeast of Brazil and their fatty acid methyl esters were analyzed by gas chromatography with flame ionization detector. The chemometric analysis consisted of principal component analysis (PCA) and hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has antibacterial and tyrosinase activity, being used in formulations for skin treatment (Nazzaro-Porro, 1987). The utility of seed FA pro les as taxonomic markers has been often observed, as in Pinaceae (Wolff et al, 2001) and Malvaceae (Fernandes et al, 2021). Mayworm and Salatino (2002) observed that the distribution of seed FA characterizes species of Qualea and Vochysia (Vochysiaceae), irrespective of the geographic location of samples of the same species.…”
Section: Discussionmentioning
confidence: 99%
“…It has antibacterial and tyrosinase activity, being used in formulations for skin treatment (Nazzaro-Porro, 1987). The utility of seed FA pro les as taxonomic markers has been often observed, as in Pinaceae (Wolff et al, 2001) and Malvaceae (Fernandes et al, 2021). Mayworm and Salatino (2002) observed that the distribution of seed FA characterizes species of Qualea and Vochysia (Vochysiaceae), irrespective of the geographic location of samples of the same species.…”
Section: Discussionmentioning
confidence: 99%